2011
DOI: 10.1016/j.jacc.2011.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Ablation of Rotors Suppresses Inducibility of Acetylcholine-Induced Atrial Fibrillation in Left Pulmonary Vein–Left Atrium Preparations in a Beagle Heart Failure Model

Abstract: Epicardial ablation of the rotor anchoring sites suppresses AF inducibility. The arrhythmogenicity at the maximal dominant frequency sites is directly/indirectly suppressed by the rotor ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Previous chronic AF dog models have demonstrated that without medication, the ventricular response rate is fast (Ͼ220 beats/min) and that heart failure develops unless AV nodal ablation or pharmaceutical interventions are used (4,23,35). Rapid ventricular pacing induces congestive heart failure in dogs when pacing rates are 220 -260 beats/min (10,28). In the present study, dogs developed significant heart failure even when the ventricular Ease of handling animals…”
Section: Discussionmentioning
confidence: 99%
“…Previous chronic AF dog models have demonstrated that without medication, the ventricular response rate is fast (Ͼ220 beats/min) and that heart failure develops unless AV nodal ablation or pharmaceutical interventions are used (4,23,35). Rapid ventricular pacing induces congestive heart failure in dogs when pacing rates are 220 -260 beats/min (10,28). In the present study, dogs developed significant heart failure even when the ventricular Ease of handling animals…”
Section: Discussionmentioning
confidence: 99%
“…RF lesions were delivered point-by-point at the area covering the focal and reentrant drivers with the use of serial applications. 10,20 When drivers were seen in the PVs, circumferential ablation of ipsilateral PVs was undertaken. The end point of regional ablation was the slowing of local electric activity.…”
Section: Rf Ablationmentioning
confidence: 99%
“…Localized drivers are difficult to detect in persistent AF with conventional techniques because of sequential temporospatial mapping, lack of specificity of complex atrial electrograms, intermittent firing, and spatial meandering. [7][8][9] Wide-field mapping tools have been used to capture these sources with the use of balloon, multispline probes 5,[10][11][12][13][14] or electrode arrays enveloping the torso. [15][16][17][18] Recent developments have allowed biatrial AF mapping using activation or phase-based analysis of body surface potentials.…”
mentioning
confidence: 99%
“…The 2 prevailing hypotheses are, first, that AF is caused by spatially meandering electrical waves (the multiwavelet hypothesis (124)) and, second, that AF is caused by electrical spiral waves (rotors) or focal beat sources from which activity disorganizes to the surrounding atrium (the localized source hypothesis (125)). Chou et al (126) provided data to support the localized source hypothesis, in Langendorff-perfused LA-pulmonary vein preparations from 13 dogs. Sustained AF was induced by rapid pacing and acetylcholine infusion and was characterized by rotors in all animals with additional focal beat sources in just over one-half.…”
Section: Mechanisms Of Human Atrial Fibrillationmentioning
confidence: 94%